If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + 3 = 14 Reorder the terms: 3 + 3p = 14 Solving 3 + 3p = 14 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 3p = 14 + -3 Combine like terms: 3 + -3 = 0 0 + 3p = 14 + -3 3p = 14 + -3 Combine like terms: 14 + -3 = 11 3p = 11 Divide each side by '3'. p = 3.666666667 Simplifying p = 3.666666667
| 12+(34-5)= | | 3(x+8)=15 | | -16x=-48 | | 5x^2-5=0 | | x-3x=8 | | 8x-9=7x-3 | | 9.4m= | | 0.5(3x+2)-0.2(x+6)=5 | | 0.33(2x+3)-0.2(x+6)=4 | | 3(n-9)=30 | | 12(x+3)=3(4x+5)+21 | | 3x^4=16x^2+12 | | 0.5(x+2)=0.25(2x+4) | | 0.2(4x+7)=3(4-4x)+15 | | 14m-2=2(8m-5) | | -5x+4= | | 21x=9x^4+6x^2+1 | | -0.16(x-18)+3(x+3)=x-6 | | 400=21x | | 9x+4=2(4x-2)+8 | | 3x^2=52x | | 4m^2n+5m^2p-4mnp= | | -3+9(x-1)=16x+4-7x | | 30x+25+-3x-3=30x-15 | | 6v-9=3(v-6) | | 9(u-6)=-7u-22 | | 7w-48=-3(w-4) | | 3x-8y=-18 | | 4(u+3)=-5u-33 | | (4x+3)(5x-6)= | | 3c+2=7c-3 | | 0.2(3x+5)-0.3(x+7)=4 |